HUBUNGAN SIKAP DAN MOTIVASI DENGAN PENERAPAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS)PADA KELUARGA DI WILAYAH KERJA PUSKESMAS GULAI BANCAH KOTA BUKITTINGGI TAHUN 2018 - Yaslina Yaslina; Bella Andini; Nofriadi Nofriadi (JURNAL KESEHATAN PERINTIS, 2018)
Based on survei result by puskesmas at 2016 from target 380 househifery obtained 201 housewifery do clean and healthy life behavior (PHBS) , and based on data obtained by public health departement (DKK) puskesmas Gulai Bancah 50,8% was doing PHBS. Purpose : the ain for this study is to known the relationship between attitude and motivation with application of clean and healthy life behavior (PHBS) in region of puskesmas Gulai Bancah Bukittinggi City 2018. Design of this study is descriptif correlation with approach of cross sectinal with 94 study sample predefined. The study used questionnaire for get information by respondent. The result of this study showed family than have good attitude (63,8%), higt motivation(69,1%) and good PHBS (60,6%. There was a relationship between attitude (P=0,002) OR= 4.442 and motivation (P=0,001) OR 4.961 with application of clean and healthy life behavior (PHBS) of housewifery in region puskesmas Gulai Bancah Bukittinggy City 2018.based on the result can be on the line that more than half housewifery have good attitude, and high motivation, and more than half housewifery have a good PHBS. The result showed that attitude and motivation have relationship wiith application of clean and healthy life behavior (PHBS). Suggest for health department can increase an effort health promotion ofapplication PHBS, so that can improve degree of community helathy.